Pengaruh Kegiatan TPA dan Motivasi Orang Tua Dalam Mengikuti TPA Terhadap Kepercayaan Diri Siswa Kelas Atas SD Muhammadiyah 15 Surakarta Tahun 2015/2016 - Pradita, Alfianita Resta Ayu, Dra. Ratnasari Diah Utami, M.Si., M.Pd (2016)
This study aimed to determine the effect of TPA activity and motivation of parents in following the TPA towards confidence-grade students in elementery school Muhammadiyah Surakarta 15 year 2015/2016. The sample population studied were all students of upper classes (IV,V VI) SD Muhammadiyah 15 Surakarta. Collecting data in this study using the technique of questionnaires, interviews and documentation as a source of research. To test instrument to test the validity and reliability testing. Then do the prerequisite test analysis including normality test and reliability test. Data analysis technique of this research is to test multiple linear hypothesis testing using t test and F. Based on the calculation hypothesis test or t test obtained tcount > ttable is 1.708> 1.703 and tcount > ttable namely 1.708> 1.703. On the test of F obtained Fcount > Ftable is 9.050> 3.37. Thus, from this study it can be concluded that there are significant TPA activity and motivation of parents of confidence upper grade students of SD Muhammadiyah Surakarta 15. Relative Contribution and Contribution Award Effective at the landfill activities SR = SE = 81.23% and 10.70%. On parental guidance for SR = 18,77% and SE = 1,70%. It can be concluded that the activities of the landfill has a bigger impact on confidence than the motivation of parents.